Impact of Production Technology on Soybean Productivity through Frontline Demonstration - Meena, D.S.; Jadon, Chaman; Meena, B.S. (Annals of Agricultural Research, 2016)
The frontline demonstrations were conducted during kharif seasons of 2005 to 2010 in the Humid South-Eastern Plain of Rajasthan to study the impact of soybean production technology. The sample size of respondent was 105, major conclusions regarding adoption indicated that highest technological gap exist in suitable high yielding variety followed by weed and insect- pest infestation. Further the study reveals that the potential yield (2.75 t/ha) can be obtained through transfer of improved technology at farmer’s field. Maximum net returns Rs 31670/ha with higher ICBR 5.27 was observed in the year 2010 as compared to farmer’s practices. Minimum yield 0.98 t/ ha received in year 2008 due to heavy infestation of Â yellow mosaic virus and charcoal rot in the crop. The knowledge of farmers was significantly increased (65.7%) after implementation of frontline demonstrations. Majority of farmers expressed medium (55.2%) to high (75.7%) level of satisfaction to the performance of improved technologies. Present results clearly show that yield of soybean can be boost up by adoption of recommended technology.